Integration of social work into specialist palliative home service - Janice Lee Wartchow; Stefan Bär; Bernd Alt-Epping; Christina Gerlach (Palliative Care and Social Practice)
Background: The specialist palliative home service (SAPV) federal framework contract for adults, to be enacted in Germany until 2028, does not legally mandate the hiring of a third professional group beyond specialist nurses and physicians, although palliative care embraces the psychosocial dimension and an interprofessional approach. Objectives: This article aims to explore the role of medical staff in integrating social work (SW) into SAPV. Design: Qualitative case study. Methods: The study utilised theoretical and qualitative quota sampling to explore barriers to integrating SW into SAPV-teams, ensuring diverse perspectives. Sequential analysis was applied to uncover collective interpretations, generating and validating interpretive hypotheses directly from the data. Results: Four physicians and four nurses from the SAPV-team based at Heidelberg University Hospital participated. The medical staff’s attributions to SW significantly impact its integration into SAPV. Their perception of the SW profession determines the extent and manner of its integration into daily practices. Attributions on SW in SAPV as determined by nurses and physicians were social-medical knowledge, counselling, being a core competence in SAPV and similarities to the profession of psychologists. In the examined case, the integration was effective, and there was a desire for an increased presence of SW because there is still a lack of their working hours, and the medical staff wished for the social workers’ presence during home visits. Conclusion: This study highlights that SAPV requires SW to be effective, nonetheless, not being considered in the new federal contract to allocate resources. Possible barriers against the integration of SW within the real-world clinical practice of palliative care should be further investigated in future studies by involving social workers’ and healthcare managers’ experiences and strategies to understand why the employment of social workers in SAPV is progressing slowly and inform strategies to enhance their integration.